Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd003827.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Gauze and tape and transparent polyurethane dressings for central venous catheters

Abstract: We found a four-fold increase in the rate of catheter related blood stream infection when a polyurethane dressing was used to secure the central venous catheter however this research was at risk of bias and the confidence intervals were wide indicating high uncertainty around this estimate; so the true effect could be as small as 2% or as high as 17-fold. More, better quality research is needed regarding the relative effects of gauze and tape versus polyurethane dressings for central venous catheter sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 24 publications
0
43
1
4
Order By: Relevance
“…The use of gauze and tape was associated with lower rates of catheter-related bloodstream infections 14 . In the present study, gauze and micropore tape were chosen for the dressings because of the possibility that the transparent film could interfere with the stability of the catheter.…”
Section: ■ Discussionmentioning
confidence: 97%
“…The use of gauze and tape was associated with lower rates of catheter-related bloodstream infections 14 . In the present study, gauze and micropore tape were chosen for the dressings because of the possibility that the transparent film could interfere with the stability of the catheter.…”
Section: ■ Discussionmentioning
confidence: 97%
“…9 All concluded that the choice of dressing can be a matter of preference but if blood is leaking from the catheter insertion site, a gauze dressing might be preferred to absorb the fluid. We identified an updated Cochrane review, 10 which concluded that bloodstream infection was higher in the transparent polyurethane group when compared with gauze and tape. The included trials were graded low quality due to the small sample size and risk of bias.…”
Section: Choose the Right Dressing For Insertion Sites To Minimise Inmentioning
confidence: 99%
“…However, the source studies for the meta-analysis reporting this association were of low quality. 203 7. Impact of the use of chlorhexidine-based products on bacterial resistance to chlorhexidine.…”
Section: Use Antiseptic-or Antimicrobial-impregnated Cvcs Inmentioning
confidence: 99%